MENEROPONG CORAK BERAGAMA FUNDAMENTALISME-RADIKALISME DALAM ISLAM - Yaqub, Andi (AL-Fikr, 2015)
This article discusses fundamental understanding and radical as the root of the conflict within Islam. Fundamentalism and radicalism are ideologies that adhere to the principle of religious literalists. According to them, the Koran and the Hadith are the basic principle of Islam that do not require interpretation. Adhering to the text of the Quran and the Hadith is literalist, fundamentalist groups made in recent years, is also suspected to be followers of radicalism. The fundamentalism and radicalism that exist today in various countries (including Indonesia), still to be recognized as one of the components of society that does not come out of Islam. Nowadays, Fundamentalism and Islamic radicalism, may be considered that its existence has entered the modern period. They Â focusing on challenge the West and there is also the fundamentalist style and radikalist not challenging the West, but trying hard to make the practice of Islamic law in a country. For the latter group, they exist and survive in Indonesia.